COMPARATIVE STUDY OF AQUEOUS AND ETHANOLIC EXTRACT OF AMORPHOPHALLUS PAEONIIFOLIUS TUBER ON CENTRAL NERVOUS SYSTEM ACTIVITY IN MICE - DEBNATH, TITIN; SEN, MALINI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the present study was to perform phytochemical screening and to carry out a comparative study on aqueous and ethanolic extract of Amorphophallus paeoniifolius tuber on central nervous system (CNS) activity in Swiss albino mice. Methods: A. paeoniifolius tuber was collected, shed dried, and powdered. Extracts of the powder were prepared separately using ethanol and water. Phytochemical screening was also done from the extract. The animals were divided in six groups. Group 1 received DMSO solution (Control). Group 2 animals received Diazepam (1.5 mg/kg, standard). Groups 3 and 4 received A. paeoniifolius aqueous extract (200 mg/kg and 400 mg/kg, respectively). Groups 5 and 6 received A. paeoniifolius ethanolic extract (200 mg/kg and 400 mg/kg, respectively). In vivo CNS activities of the extracts were checked by actophotometer, rotarod, and forced swim test. Results: The extracts show presence of alkaloids, flavonoids, steroids, terpenoids, reducing sugar, carbohydrate, and tannin. The aqueous and ethanolic extract of A. paeoniifolius tuber showed significant decrease in locomotor activity when compared to control. Among the extracts, the 400 mg/kg ethanolic extract shows maximum CNS depression. All the extracts showed significant muscle relaxant similar to the standard drug. The extracts also exhibited significant increase in immobility time in a dose-dependent manner in forced swim test. Conclusion: The aqueous and ethanolic extract of A. paeoniifolius tuber (200 mg/kg, 400 mg/kg) shows significant CNS depressant and muscles relaxant and anxiolytic properties.